2018
DOI: 10.4110/in.2018.18.e10
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor 1/2 Agonist Pam3CSK4 Suppresses Lipopolysaccharide-driven IgG1 Production while Enhancing IgG2a Production by B Cells

Abstract: Interaction between pathogen-associated molecular patterns and pattern recognition receptors triggers innate and adaptive immune responses. Several studies have reported that toll-like receptors (TLRs) are involved in B cell proliferation, differentiation, and Ig class switch recombination (CSR). However, roles of TLRs in B cell activation and differentiation are not completely understood. In this study, we investigated the direct effect of stimulation of TLR1/2 agonist Pam3CSK4 on mouse B cell viability, prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…This sequential recognition of HSV-1 must occur within the same DCs upon direct recognition of the virus and not through activation of bystander DCs ( 10 ). Similarly, it is thought that this sequential recognition of HSV-1 by TLR2 and TLR9 occurs in NK cells because TLR2 is expressed on the surface of NK cells, whereas TLR9 has an intracellular localization overlapping with the Golgi apparatus ( 60 , 61 ). Also, since TLR2 and TLR9 use the same adaptor molecule, MyD88, to transmit signals to a cascade of MAPKs that induces transcriptional expression of inflammatory cytokines ( 52 ), dual and sequential recognition of HSV-1 by TLR2 and TLR9 is assumed to amplify their intracellular signal in NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…This sequential recognition of HSV-1 must occur within the same DCs upon direct recognition of the virus and not through activation of bystander DCs ( 10 ). Similarly, it is thought that this sequential recognition of HSV-1 by TLR2 and TLR9 occurs in NK cells because TLR2 is expressed on the surface of NK cells, whereas TLR9 has an intracellular localization overlapping with the Golgi apparatus ( 60 , 61 ). Also, since TLR2 and TLR9 use the same adaptor molecule, MyD88, to transmit signals to a cascade of MAPKs that induces transcriptional expression of inflammatory cytokines ( 52 ), dual and sequential recognition of HSV-1 by TLR2 and TLR9 is assumed to amplify their intracellular signal in NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the synthetic bacterial lipopeptide Pam3CSK4 is an effective activator of the NF-κB and IRF pathway. TLR-induced NF-κB and IRF signaling mediates the expression of pro-inflammatory factors including TNFα, IL-1β, IL-6, IL-8, C-C motif ligand-5 (CCL-5), and monocyte chemoattractant protein-1 (MCP-1) [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…The mouse B lymphoma cell line CH12F3-2A (surface μ + ) was provided by Dr. T. Honjo (Kyoto University, Kyoto, Japan). Mouse spleen resting B cells were obtained by depletion of CD43 + cells using anti-CD43 microbeads and high-gradient magnetic cell separation according to the manufacturer's instruction (MACS; Miltenyi Biotec, Bergisch Gladbach, Germany) as previously described [5]. The purity of resting B cells (CD43 − B220 + ) was assessed using FACSCalibur (BD Biosciences, San Jose, CA, USA) following staining of the cells with anti-CD43 FITC (eBioscience, San Diego, CA, USA) and anti-B220 PE (BD Biosciences) (Supplementary ).…”
Section: Methodsmentioning
confidence: 99%
“…TLR signaling can directly affect B cell functions, even without the support of T cells [14]. We recently reported that TLR1/2 agonist Pam3CSK4 and TLR7 agonist imiquimod directly inhibit IgG1 and IgE class switching, respectively, in activated mouse B cells [5, 6]. In addition, we found that Dectin-1 (a type of CLR) agonist selectively induced IgG1 class switching by TLR4 agonist lipopolysaccharide (LPS)-activated mouse B cells [7, 8].…”
Section: Introductionmentioning
confidence: 99%